Lossless compression handbook - Sayood, Khalid (Academic Press series in communications, networking and multimedia)
The 21 chapters in this handbook are written by the leading experts in the world on the theory, techniques, applications, and standards surrounding lossless compression. As with most applied technologies, the standards section is of particular importance to practicing design engineers. In order to create devices and communication systems that can communicate and be compatible with other systems and devices, standards must be followed. *Clearly explains the process of compression and transmission of multimedia signals *Invaluable resource for engineers dealing with image processing, signal processing, multimedia systems, wireless technology and more.